Investigating the effectiveness of debt management practices on the performance of a company: case DHL International (Zimbabwe) - Mlambo, Nancy (Midlands State University, 2018)
Due to difficulties with limited financial resources available to operators of the market, there is no doubt of an increase in credit transactions as they will be trying to have a sale but there are effects that follow depending on the firm’s management of debtors. DHL Zimbabwe has been facing higher financial challenges as it has been experiencing a rapid increase in bad debts written off and a continuous decrease in revenue thus threatening its cash flows and performance. Therefore, it was now a concern of the researcher to investigate on the effectiveness of debtors’ management practices on the performance of DHL Zimbabwe. The aim of the research was to understand the practices of debtors’ management at the organization, guidelines in place to implement the practices, personnel responsible for formulation and implementation of the practices. It was also the objective of this research to identify controls which are in place over debt collection and the challenges that were being faced by the entity in managing its debtors. Also the research aimed at recommending the best practices that can be instituted towards debt management basing on research findings and literature review. A review of related literature was also carried out in a bid to establish what other renowned authors had had to say on the issue of debt management. The study used descriptive research design where there was both use of questionnaires and interviews because of its flexibility. Sources of data, research instruments, populations and samples were given in the research. Primary data was presented using diagrams, pie charts and tables, to illustrate research findings and responses gathered. Research findings showed that, debt factoring, payment plans, timely follow ups, rotation of debt collection staff, cutting supply to customers who are failing to meet their obligations and prepayments and early payments discount can improve debt collection in the organization. As a result, the research recommended that the organization should establish the best practices highlighted in the research.